2014
DOI: 10.1128/mcb.00104-14
|View full text |Cite
|
Sign up to set email alerts
|

The Canonical Wnt Signal Restricts the Glycogen Synthase Kinase 3/Fbw7-Dependent Ubiquitination and Degradation of Eya1 Phosphatase

Abstract: Haploinsufficiency of Eya1 causes the branchio-oto-renal (BOR) syndrome, and abnormally high levels of Eya1 are linked to breast cancer progression and poor prognosis. Therefore, regulation of Eya1 activity is key to its tissue-specific functions and oncogenic activities. Here, we show that Eya1 is posttranslationally modified by ubiquitin and that its ubiquitination level is selflimited to prevent premature degradation. Eya1 has an evolutionarily conserved CDC4 phosphodegron (CPD) signal, a target site of gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…When lysates of cells expressing cMyc or EYA1 alone, or both, were immunoprecipitated using antiFlag-EYA1, cMyc and endogenous FBW7 were also coprecipitated (Fig. 10B), suggesting that FBW7 and EYA1 form a complex in vivo, consistent with the report that FBW7 binds to EYA1 in vivo (24). In sum, these results suggest that EYA1 regulates cMyc stability by affecting the degradation machinery through binding to cMyc and regulation of the phospho-T58-Myc levels, which in turn impairs the recruitment of FBW7 to cMyc, subsequently leading to reduced ubiquitination of Myc.…”
Section: Fig 4 Nmr Analysis (A)supporting
confidence: 84%
“…When lysates of cells expressing cMyc or EYA1 alone, or both, were immunoprecipitated using antiFlag-EYA1, cMyc and endogenous FBW7 were also coprecipitated (Fig. 10B), suggesting that FBW7 and EYA1 form a complex in vivo, consistent with the report that FBW7 binds to EYA1 in vivo (24). In sum, these results suggest that EYA1 regulates cMyc stability by affecting the degradation machinery through binding to cMyc and regulation of the phospho-T58-Myc levels, which in turn impairs the recruitment of FBW7 to cMyc, subsequently leading to reduced ubiquitination of Myc.…”
Section: Fig 4 Nmr Analysis (A)supporting
confidence: 84%
“…EYA activity could be regulated by multiple signaling pathways. Dr. Li and her coworkers demonstrated that hyperactivation of the canonical Wnt and PI3K/Akt signaling pathways reduces EYA1 ubiquitination and thus prevents its premature degradation [85]. In particular, PI3K/Akt signaling was shown to repress the SUMOylation of EYA1 in a phosphorylation-dependent manner and thus enhance the transcriptional activity of EYA1 [86].…”
Section: Potential Strategy Of Targeting the Rdgn Pathway For Clinicamentioning
confidence: 99%
“…The striking agreement between the peptides and proteins observed in the plasma of breast cancer patients and the previous literature on breast cancer tumors, adjacent fluids, cell lines or blood fluids indicates that LC–ESI–MS/MS of blood peptides will be a powerful tool for selecting plasma proteins and peptides for further research and confirmation. The results of mass spectrometry show striking agreement with previous genetic or biochemical experiments on cancer tissues, tumors, biopsies or cell lines: CPEB1 [63], LTBP4 [64], HIF1A [65, 66], IGHE [67], RAB44 [68], NEFM [39], C19orf82, SLC35B1 [69], 1D12A that shows a cyptic alignment with cyclin-dependent kinase-like isoform 1 [70], C8orf34 [71], OCLN [72], EYA1 [73], HLA-DRB1 [74], LAR [75] and LRRC4B that interacts with the LARS receptor phosphatases [76], PTPDC1 [77], WWC1 [78], ZNF562, PTMA [79], MGAT1 [80], NDUFA1 [81], NOGOC [82], olfactory receptors OR1E or the HSA12 protein [83], GCSH [84], ELTD1 [85], TBX15 [86], orphan nuclear receptors such as NR2C2 [87], autophagy related proteins such as ATG16L1 (FLJ00045) that regulate the production of extracellular vesicles called exosomes [88], PDLIM1 [89, 90], GALNT9 [91], ASH2L [92], PPFIBP1 [93], SLCO3A1 [94], BHMT2 [95], CS citrate synthase [96] FAM188B2 inactive ubiquitin carboxyl-terminal hydrolase MINDY4B that is expressed in breast cancer tissue, LGALS7 [97] SAT2 [98], SFRS8, SLC22A12 [99], WNT9B [100], SLC2A4 [101], ZNF101, WT1 (Wilms Tumor Protein) [102], CCDC47 [103], ERLIN1 (SPFH1) and MREG [104], EID2 [105], THOC1 [106, 107], DDX47 [108], PTPRE [109], EMILIN1 [110], DKFZp779G1236 (piccolo, or piBRCA2) [111], MAP3K8 [112] regulated by Serine/Arginine-Rich Splicing Factor Kinase [113], QSER1 [39], IQCJ-SCHIP1 [114, 115], ANXA4 [116] and DHDDS [117] among others. The disease-specific proteins and peptides may result from the introduction of new proteins into cir...…”
Section: Discussionmentioning
confidence: 99%